COMPOSITE MEMBRANES OF POLY(1-TRIMETHYLSILYL-1-PROPYNE) AND POLY(DIMETHYL SILOXANE) AND THEIR PERVAPORATION PROPERTIES FOR ETHANOL-WATER MIXTURE - KANG, YS; SHIN, EM; JUNG, B; KIM, JJ (JOHN WILEY & SONS INC, 1994)
A poly(1-trimethylsilyl-1-propyne) (PTMSP) membrane was systematically modified to prevent flux decline over time by incorporating poly (dimethyl siloxane) (PDMS) in three different ways: (1) semi-interpenetrating polymer network (I series), (2) PDMS sorption (S series), and (3) PDMS sorption and crosslinking (X series). The PTMSP and PDMS phases were partially mixed in the I series, which was confirmed by the measurement of density and glass transition temperature. The flux and separation factor in pervaporation of an ethanol-water mixture decrease with time for the I series, analogous to the behavior of pure PTMSP. However, the flux and separation factor remained steady with time in the case of the S and X series. The sorption method appears to be a good means for maintaining a time-unvarying flux and separation factor at a minimum expense. (C) 1994 John Wiley & Sons, Inc.
Keywords: SUBSTITUTED-POLYACETYLENE MEMBRANES; CHEMICAL MODIFICATION; GRAFT COPOLYMER; POLY(SUBSTITUTED-ACETYLENE); SORPTION; GAS; POLY<1-(TRIMETHYLSILYL)-1-PROPYNE>; PERMEABILITY; SEPARATION; PERMEATION